1990
DOI: 10.1002/jbm.820240407
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility of a polyether urethane, polypropylene oxide, and a polyether polyester copolymer. A qualitative and quantitative study of three alloplastic tympanic membrane materials in the rat middle ear

Abstract: The biocompatibility of porous implants made of Estane 5714 F1 polyether urethane, polypropylene oxide, and a poly(ethylene oxide hydantoin) and poly(tetramethylene terephthalate) segmented polyether polyester copolymer (HPOE/PBT copolymer), which were selected as candidates for an alloplastic tympanic membrane, was assessed after implantation in rat middle ears for periods of up to 1 year. Implantation of the materials led to tissue reactions initially associated with the wound-healing process, whereas after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(42 citation statements)
references
References 31 publications
0
42
0
Order By: Relevance
“…37 Since their discovery, many bioactive ceramics have been used for bone reconstruction surgery in clinical situations and have been reported to show excellent results. In addition, some nonceramic materials such as calcium carbonate crystals (aragonite and calcite) [38][39][40][41] and organic polymers [42][43][44][45] have been reported to show bone-bonding characteristics. Bone is formed by cells called osteoblasts, which arise from progenitor cells in a multistep lineage cascade.…”
Section: Introductionmentioning
confidence: 98%
“…37 Since their discovery, many bioactive ceramics have been used for bone reconstruction surgery in clinical situations and have been reported to show excellent results. In addition, some nonceramic materials such as calcium carbonate crystals (aragonite and calcite) [38][39][40][41] and organic polymers [42][43][44][45] have been reported to show bone-bonding characteristics. Bone is formed by cells called osteoblasts, which arise from progenitor cells in a multistep lineage cascade.…”
Section: Introductionmentioning
confidence: 98%
“…PEGT/PBT copolymer degradation has been analyzed in other studies and proceeds mainly via mechanisms of hydrolysis, oxidation, and phagocytosis [15,[28][29][30]44,45]. Deschamps et al [45] showed not only that during accelerated hydrolysis of the copolymer a decrease in copolymer MW is mainly caused via scission of the ester bonds connecting the PEG and terephthalate, but that cleavage in the PBT hard segment also occurred.…”
Section: Discussionmentioning
confidence: 99%
“…By variation in the weight percentage and/or length of the soft and hydrophilic PEGT segment, copolymers can be prepared differing in hydrophilicity, pliability, mechanical integrity, degradation rate, and cell-adhesion affinity. Furthermore, the PEGT/PBT copolymer has already been introduced to the clinic as a degradable scaffold for the repair of tympanic membranes [14,15] more than 15 years ago. More recently the FDA approved it as a cement restrictor in orthopedics [16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Various studies have been performed to assess the biocompatibility of these degradable PEGT/PBT copolymers upon implantation in soft and hard tissue. [2][3][4][5][6][7][8] It was concluded that PEGT/PBT copolymers did not induce any adverse affect on the surrounding tissue and thus showed satisfactory biocompatibility. Clinical studies have been performed using PEGT/PBT copolymers as an artificial tympanic membrane, 9,10 ventilation tubes, an adhesion barrier, 11 a cement restrictor, bone fillers, [12][13][14] elastic bioactive coatings on load-bearing dental and hip implants, [15][16][17] and also for wound healing purposes.…”
Section: Introductionmentioning
confidence: 99%